Osteoprotective effect by interleukin-4 (IL-4) on lipoprotein-induced periodontitis - Lima Teixeira, Jorge F. [UNESP]; Henning, Petra; Cintra Magalhães, Fernando A.; Coletto-Nunes, Glaucia [UNESP]; Floriano-Marcelino, Thais [UNESP]; Westerlund, Anna; Movérare-Skrtic, Sofia; Oliveira, Guilherme J.P.L.; Lerner, Ulf H.; Souza, Pedro Paulo C. (Elsevier, 2023)
Lipoproteins are immunostimulatory bacterial components suggested to participate in inflammation-induced bone loss in periodontal disease through stimulation of osteoclast differentiation. Toll-like receptor 2 activation by Pam2CSK4 (PAM2), known to mimic bacterial lipoproteins, was previously shown to enhance periodontal bone resorption in mice. The anti-inflammatory cytokine interleukin-4 (IL-4) is a known inhibitor of RANKL-induced bone resorption in vitro. Here, we have investigated whether IL-4 could decrease PAM2-induced periodontal bone loss and osteoclastogenesis in vivo. In a model of periodontitis induced by gingival injections of PAM2 in mice, concomitant injections of IL-4 reduced bone loss. Histologically, IL-4 reduced the recruitment of inflammatory cells and the formation of TRAP+ osteoclasts stimulated by PAM2. Mouse bone marrow macrophages (BMMs) and neonatal calvarial osteoblasts were used to assess the effect of IL-4 on PAM2-induced osteoclastogenesis in vitro. In RANKL-primed BMMs stimulated by PAM2 Nfatc1, Ctsk, and Acp5 gene expression was up-regulated and resulted in robust formation of TRAP+ multinucleated osteoclasts, effects which were impaired by IL-4. These effects were mediated by impairment in PAM2-induced c-fos expression. In primary calvarial osteoblast cultures, IL-4 decreased PAM2-induced Tnfsf11 (encoding RANKL) mRNA and enhanced Tnfrsf11b (encoding OPG) expression. Our data demonstrate that the osteoprotective effect by IL-4 on lipoprotein-induced periodontal disease occurs through the inhibition of osteoclastogenesis by three mechanisms, one by acting directly on osteoclast progenitors, another by acting indirectly through decreasing the expression of osteoclast-regulating cytokines in osteoblasts and a third by decreasing inflammation.
Keywords: Bone resorption; IL-4; Inflammation; Osteoclasts; Periodontitis